P137 Supporting patients to get the best from their osteoporosis treatment; what works for whom, why and in what circumstance: a rapid realist review. (23rd April 2022) - Paskins, Zoe; Babatunde, Opeyemi; Sturrock, Andrew; Toh, Li Shean; Horne, Robert; Maidment, Ian
Abstract: Background/Aims: For two decades, clinicians and academics have been writing about the problem of poor adherence in osteoporosis, while people with osteoporosis have identified a need for more follow up and information about medicines. We aimed to understand what works in supporting people with osteoporosis to get the best from their medicines, and specifically, to understand what mechanisms enable components of interventions to support osteoporosis medication optimisation and the underlying contextual conditions that enabled these mechanisms. Methods: We conducted a Rapid Realist Review. The scope was informed by a workshop of the Effectiveness Working Group of the Royal Osteoporosis Society Osteoporosis and Bone Research Academy and the approach informed by background syntheses of qualitative literature and the Perceptions and Practicalities Approach as an underpinning conceptual framework. A primary search identified observational or interventional studies which aimed to improve medicines adherence or optimisation. Included studies were assessed for quality and data extracted relating to context, mechanism and outcomes. A supplementary second search was conducted to gain additional insight on included key papers and emerging mechanisms. Extracted data were interrogated by authors independently for patterns of context-mechanism-outcome configurations and further discussed in weekly team meetings. Recommendations for research and clinical practice were co-developed with clinical and lay stakeholders. Results: 41 papers were included. We identified five contextual timepoints for the person with osteoporosis (identifying a problem; starting medicine; continuing medicine) and the practitioner and healthcare system (making a diagnosis and giving a treatment recommendation; reviewing medicine) and mechanisms relating to patient informed decision making, treatment burden, supporting routinisation and memory, supporting clinical decision making, targeting support, and approaches which were integrated and sustainable. Interventions which support patient informed decision making, improve patient knowledge and understanding, have potential to influence long-term commitment to treatment, although few studies explicitly addressed patients' perceptions of illness and treatment as recommended in NICE guidelines. During treatment, targeting additional consultations to those most in need may be a cost and clinically effective approach to enable this. Supporting primary care clinician decision making and integration of primary and secondary care services also appears to be important, in improving rates of treatment initiation and adherence. Supporting patients' ability to adhere (eg by lowering treatment burden and issuing reminders) may be helpful to address practical difficulties but there is little evidence to support the use of reminders alone. Conclusion: For medicines optimisation for people with osteoporosis, we suggest a need for more patient-centred interventions to address patients' perceptions of illness and treatment, and reduce treatment burden. Specialist services should consider the extent to which they integrate with, and support primary care clinical decision-making, in order to impact long-term clinical outcomes. Specific research recommendations have been co-developed, to address these knowledge gaps. Disclosure: Z. Paskins: Grants/research support; NIHR, Versus Arthritis, Royal Osteoporosis Society. O. Babatunde: None. A. Sturrock: None. L. Toh: None. R. Horne: None. I. Maidment: None.